Change in anti-nutritional and reducing sugar value during germination in some varieties of finger millet in Nepal. - Khadka, Abhishek. (Tufts University. Tisch Library., 2016)
This poster presents on the nutritional content of 6 different kinds of millet, and some innovative processes to reduce the anti-nutritional factors contained in the grain. Presented at the 2014 Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2014.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy